2011
DOI: 10.5465/amj.2011.64870139
|View full text |Cite
|
Sign up to set email alerts
|

Person-Organization Value Congruence: How Transformational Leaders Influence Work Group Effectiveness

Abstract: Using multilevel structural equations modeling, we examine the extent to which the influence of transformational leadership on work group effectiveness flows through follower perceptions of person-organization or person-supervisor value congruence. Results indicate that the group-level effect of transformational leadership on work group effectiveness was fully accounted for by the group-level impact of transformational leadership on follower perceptions of person-organization value congruence, not by its impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
223
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(238 citation statements)
references
References 73 publications
(129 reference statements)
6
223
1
3
Order By: Relevance
“…Additionally, educational level and organizational tenure were controlled for because they constitute proxies for knowledge and experience, which are important for individual creativity (Amabile, 1983). Time with supervisor was controlled for as research has suggested that time with supervisor may influence the impact of transformational leadership on employee outcomes (Hoffman, Bynum, Piccolo, & Sutton, 2011;Shin & Zhou, 2007). At the unit level, we controlled for organization membership as organizational factors may compound the influence of leaders.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, educational level and organizational tenure were controlled for because they constitute proxies for knowledge and experience, which are important for individual creativity (Amabile, 1983). Time with supervisor was controlled for as research has suggested that time with supervisor may influence the impact of transformational leadership on employee outcomes (Hoffman, Bynum, Piccolo, & Sutton, 2011;Shin & Zhou, 2007). At the unit level, we controlled for organization membership as organizational factors may compound the influence of leaders.…”
Section: Methodsmentioning
confidence: 99%
“…In order to gain emotional or mental proximity to their employees, leaders must gain trust, listen well, promote dialogue, and encourage the expansion of certain employees' roles beyond their job descriptions to include being brand ambassadors, thought leaders, and storytellers (Groysberg & Slind, 2012). Effective leadership is characterized by an alignment between the values of the leader and the values of the organization; when this alignment is present, the probability of successful leadership increases (Hoffman, Bynum, Piccolo, & Sutton, 2011). This observation fits with Adler, Heckscher and Prusak' s (2011) fmding that creating a shared purpose for a group, promoting organizational collaboration, and intentionally aligning processes in order to connect people are all factors that contribute to an organization ' s overall success.…”
Section: Organizational Leadership and Communicationsupporting
confidence: 67%
“…In order to align with the organization, Public Health needs to link the values and information being presented back to the organizations goals (Hoffman, Bynum, Piccolo, & Sutton, 2011).…”
Section: Organizational Leadership and Communicationmentioning
confidence: 99%
“…The variables were chosen based on analyses of literature on factors affecting adaptability to various environmental demands. such phenomena as: work performance and work attitudes [3,4], turnover [5], teamwork effectiveness [6], organizational citizenship behaviors [7,8], creativity [9], stress and well-being [10]. In the theory, 2 core dimensions of P-O are distinguished: supplementary and complementary fit [11].…”
Section: Introductionmentioning
confidence: 99%